The Impact of the Local Administration Efficiency in Achieving Development Programs in the State of Salalah: The Role of Customs and Traditions as a Moderating Variable - Ahmed Mahad Ahmed Bait Fadhil; Ishaq Ibrahim (OCERINT International Organization Center of Academic Research, 2024)
Non-Indexed Publication